Selenium nanoparticles coated with polysaccharide-protein complexes from abalone viscera improve growth and enhance resistance to diseases and hypoxic stress in juvenile Nile tilapia (Oreochromis niloticus). Issue 134 (March 2023) - Ni, Jing; Ren, Lirong; Ma, Ying; Xiong, Hejian; Jian, Wenjie
Abstract: The use of selenium nanoparticles (SeNPs) in aquaculture has been increasing gradually over the past few years. SeNPs enhance immunity, are highly effective against pathogens, and have low toxicity. In this study, SeNPs were prepared using polysaccharide-protein complexes (PSP) from abalone viscera. The acute toxicity of PSP-SeNPs to juvenile Nile tilapia and their effect on growth performance, intestinal tissue structure, antioxidation capacity, hypoxic stress, and Streptococcus agalactiae infection were investigated. The results showed that the spherical PSP-SeNPs were stable and safe, with an LC50 of 13.645 mg/L against tilapia, which was about 13-fold higher than that of sodium selenite (Na2 SeO3 ). A basal diet supplemented with 0.1–1.5 mg/kg PSP-SeNPs improved the growth performance of tilapia juveniles to a certain extent, increased the intestinal villus length, and significantly enhanced the activities of liver antioxidant enzymes, including superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and catalase (CAT). PSP-SeNPs also enhanced the resistance of tilapia to hypoxic stress and Streptococcus agalactiae infection, with supplementation at 0.1–0.3 mg/kg exerting more obvious effects than 1.5 mg/kg. However, PSP-SeNPs at a concentration of 4.5 mg/kg and Na2 SeO3 at 0.3 mg/kg negatively affected the growth, gut health, and the activity of the antioxidant enzymes of tilapia. Quadric polynomial regression analysis revealed that 0.1–1.2 mg/kg was the optimal PSP-SeNP supplementation concentration for tilapia feeds. The findings of this study lay a foundation for the application of PSP-SeNPs in aquaculture. Highlights: PSP-SeNPs were 13-fold safer than sodium selenite. PSP-SeNPs enhanced the activity of antioxidant enzymes. PSP-SeNPs improved the hypoxic stress resistance of juvenile tilapia. PSP-SeNPs enhanced the resistance of tilapia to Streptococcus agalactiae.